2012
DOI: 10.1098/rsbl.2012.0029
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic asymmetry: unreliable signals mask asymmetric performance of crayfish weapons

Abstract: Animals commonly use their limbs as signals and weapons during territorial aggression. Asymmetries of limb performance that do not relate to asymmetries of limb size (cryptic asymmetry) could substantially affect disputes, but this phenomenon has not been considered beyond primates. We investigated cryptic asymmetry in male crayfish (Cherax dispar), which commonly use unreliable signals of strength during aggression. Although the strength of a chela can vary by an order of magnitude for a given size, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Takeuchi et al (2008) suggested that shrimp has an innate left-right lateral movement ability in terms of their escape direction, which may affect prey-predator interactions. Crayfish use their limbs during aggression; asymmetries of limb performance could affect this behavior (Angilletta and Wilson 2012). Levin et al (2016) have suggested that left and right asymmetries in organisms arise from embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Takeuchi et al (2008) suggested that shrimp has an innate left-right lateral movement ability in terms of their escape direction, which may affect prey-predator interactions. Crayfish use their limbs during aggression; asymmetries of limb performance could affect this behavior (Angilletta and Wilson 2012). Levin et al (2016) have suggested that left and right asymmetries in organisms arise from embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Dishonest signaling of strength is quite common in some species of insects (Steger and Caldwell 1983;Adams and Caldwell 1990) and crustaceans (Backwell et al 2000;Lailvaux et al 2009;Walter et al 2011;Angilletta and Wilson 2012). Our data showed that more than 20% of males had regenerated claws, which are weaker than the originals, but strongly resemble the original claws in length.…”
Section: Bluff and Counter-bluff Tacticsmentioning
confidence: 52%
“…Although there must be limits on how often deceptive signals can be used before they lose their effect (Maynard Smith and Harper 2003), each signaling system allows some admixture of deception as long as the signal response is adaptive on average (Semple and McComb 1996;Searcy and Nowicki 2005). Indeed, dishonest signaling is commonly seen in the animal world (e.g., Steger and Caldwell 1983;Adams and Caldwell 1990;Backwell et al 2000;Candolin 2000;Elwood et al 2006;Wilson et al 2007;Munoz et al 2008;Lailvaux et al 2009;Walter et al 2011;Angilletta and Wilson 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Left-right asymmetry is a characteristic of the brain from vertebrate species and some invertebrate species [24], which arises from embryogenesis in the organism [25][26][27]. Crustacean decapods showed the left and right asymmetry in some anatomical regions [28][29][30]. Besides, some functional properties are asymmetric, as examples, lateral movement towards escape direction in shrimp [29], and the performance of limbs during aggressive behavior of crayfish [30].…”
Section: Introductionmentioning
confidence: 99%
“…Crustacean decapods showed the left and right asymmetry in some anatomical regions [28][29][30]. Besides, some functional properties are asymmetric, as examples, lateral movement towards escape direction in shrimp [29], and the performance of limbs during aggressive behavior of crayfish [30]. The sixth AG develops from two embryonic neuromeres in the crayfish Procambarus clarkii [31,32].…”
Section: Introductionmentioning
confidence: 99%